Mentoring and Professional Development: A Gateway to Professionalism - Pandey, Shiva Ram; Sharma, Mani Ram (Yayasan Sembilan Pemuda Indonesia, 2022)
This article presents ideas on mentoring and professional development. It briefly describes the needs, practices and benefits of mentoring for the professional development of teachers. It discusses teaching as a profession and teacher development. Both mentoring and professional development go hand in hand to maximize teaching and learning process. In teaching profession, mentoring is a process in which a more experienced senior teacher supports the novice teachers by providing required guidance, counseling, ideas and information on carrying out the professional responsibilities successfully. The article concludes with the idea that mentoring helps novice teachers to grow and develop personally, professionally and institutionally. Mentoring is one of the great means to achieve professionalism in teaching.